Cattle Fencing BMP Can Reduce Phosphorus Loads from Florida Ranches - Sanjay Shukla; Wendy D. Graham; Alan Hodges; James M. Knowles (EDIS)
BMPs are an important tool in helping the state and individual landowners protect and enhance state’s waters. Given the water quality issues facing Lake Okeechobee and other sensitive water bodies, the importance of BMP implementation has increased since their official establishment as part of the FWRA. In order to ensure that BMPs are reducing nutrient loadings, on-farm research is needed to verify BMP effectiveness. A four-year study was conducted to evaluate the effectiveness of the cow/calf stream fencing BMP. The study concluded that the BMP did reduce the amount of P being discharged from the ranch. This BMP should continue to be included in the cow/calf BMP manual, and, hopefully, its widespread implementation will help the state in meeting its TMDLs. This 3-page fact sheet was written by Sanjay Shukla, Wendy D. Graham, Alan Hodges, and James M. Knowles, and published by the UF Department of Agricultural and Biological Engineering, May 2014.